Pleuroparenchymal fibroelastosis with positive MPO-ANCA diagnosed with a CT-guided percutaneous needle biopsy. (24th February 2018) - Yamakawa, Hideaki; Oda, Tsuneyuki; Baba, Tomohisa; Ogura, Takashi
Abstract : A 67-year-old woman was referred to our hospital because of gradually increasing dyspnoea on exertion for 6 months. Chest CT scan showed subpleural parenchymal fibrotic opacities with traction bronchiectasis in the bilateral upper lung fields. Serum rheumatoid factor and myeloperoxidase-antineutrophil cytoplasmic antibody (MPO-ANCA) were positive. There was no evident reason to suspect connective tissue disease such as ANCA-associated vasculitis or rheumatoid arthritis. We performed a CT-guided percutaneous needle biopsy of the subpleural lesion that showed slight uptake on the fluorodeoxyglucose-positron emission tomography (FDG-PET) CT scan. This specimen showed subpleural fibrosis as evidenced by an abnormal increase of elastic tissue and minimal collagen deposition, which indicated pleuroparenchymal fibroelastosis (PPFE). Although PPFE can be associated with a variety of causes, its association with MPO-ANCA is unknown. A CT-guided transthoracic lung biopsy caused no adverse events and was useful in the diagnosis of PPFE in our patient.